DEVELOPING OF ELECTRONIC TEACHING MATERIAL BASED ON MOBILE LEARNING IN THE WAVE SUBJECTS - Rifâ€™ati, D. H. (Jurnal Pendidikan Fisika Indonesia, 2015)
In the advanced and modern era, technological sophistication led to learning which initially runs, in which teachers and students meet each other and communicate in the classroom, can be implemented through of information technology. Along with the development of information, where books and teachers who initially as a primary source of learning, are now beginning to experience growth from the internet. Mobile learning defined as mobile devices that are used in the learning process. The wave course is one of subject that must be taken by students of physics education in the third semester. This course emphasizes the concepts of wave were reviewed mathematically and the phenomenon that occurs in everyday life. Mobile learning developed in this study in the form of electronic teaching materials on subjects of waves. The aim of this study was to develop electronic teaching material in the form of mobile learning. The sample of this study is 80 students in the third semester students who are taking waves courses. The results show that mobile learning that has been developed has score 3.8 and included valid criteria.Â Pada era yang serba maju dan modern, kecanggihan teknologi menyebabkan pembelajaran yang awalnya berjalan satu arah, dimana guru dan siswa saling bertemu dan berkomunikasi di dalam kelas, dapat dilaksanakan melalui bantuan teknologi.informasi. Seiring dengan perkembangan informasi, buku dan guru yang awalnya sebagai sumber belajar utama, saat ini sudah mulai mengalami perkembangan dimana sumber belajar yang berasal dari internet sudah mulai sering dimanfaatkan dalam proses pembelajaran. Mobile larning didefinisikan sebagai perangkat mobile yang dipergunakan dalam proses belajar mengajar. Mata kuliah gelombang sendiri merupakan salah satu mata kuliah yang wajib ditempuh oleh mahasiswa program studi pendidikan fisika semester 3. Mata kuliah ini menekankan pada konsep gelombang yang ditinjau secara matematis dan fenomenanya yang terjadi dalam kehidupan sehari-hari dalam bentuk bahan ajar elektronik. Tujuan dari penelitian ini adalah untuk mengembangkan bahan ajar elektronik dalam bentuk mobile learning. Adapun sampel dari penelitian ini adalah 80 mahasiswa semester 3 yang sedang menempuh mata kuliah gelombang. Hasil penelitian menunjukkan bahwa mobile learning yang sudah dikembangkan memiliki score validasi 3.8 dan termasuk dalam kriteria valid